P-selectin promotes neutrophil extracellular trap formation in mice - Etulain, Julia (Blood, 2015)
Neutrophil extracellular traps (NETs) can be released in the vasculature. In addition to trapping microbes, they promote inflammatory and thrombotic diseases. Considering that P-selectin induces prothrombotic and proinflammatory signaling, we studied the role of this selectin in NET formation. NET formation (NETosis) was induced by thrombin-activated platelets rosetting with neutrophils and was inhibited by anti-P-selectin aptamer or anti-P-selectin glycoprotein ligand-1 (PSGL-1) inhibitory antibody but was not induced by platelets from P-selectin(−/−) mice. Moreover, NETosis was also promoted by P-selectin–immunoglobulin fusion protein but not by control immunoglobulin. We isolated neutrophils from mice engineered to overproduce soluble P-selectin (P-selectin(ΔCT/ΔCT) mice). Although the levels of circulating DNA and nucleosomes (indicative of spontaneous NETosis) were normal in these mice, basal neutrophil histone citrullination and presence of P-selectin on circulating neutrophils were elevated. NET formation after stimulation with platelet activating factor, ionomycin, or phorbol 12-myristate 13-acetate was significantly enhanced, indicating that the P-selectin(ΔCT/ΔCT) neutrophils were primed for NETosis. In summary, P-selectin, cellular or soluble, through binding to PSGL-1, promotes NETosis, suggesting that this pathway is a potential therapeutic target for NET-related diseases.